2018
DOI: 10.1016/j.ejvs.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Patency of Tibial Run Off Arteries on Clinical Outcomes After Stenting for Chronic Total Occlusions in the Superficial Femoro-popliteal Artery

Abstract: WHAT THIS PAPER ADDS After angioplasty of an occluded superficial femoral or popliteal artery, interventionalists face the dilemma of what to do with occlusive disease of the tibial arteries. This study shows that the patency of the tibial arteries is an important predictor of mid-term patency of the femoropopliteal artery and that a successful tibial percutaneous transluminal angioplasty improves clinical outcome. These findings suggest that percutaneous transluminal angioplasty for chronic total occlusions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“… 1 Certain characteristics have been demonstrated to confer higher risk of major adverse cardiovascular events (MACE) or major adverse limb events (MALE) following PVI, such as diabetes, 2 , 3 , 4 chronic kidney disease (CKD), 5 , 6 concomitant coronary artery or cerebrovascular disease, 7 , 8 and certain lesion characteristics. 2 , 9 , 10 , 11 However, the relationships between these factors have not been well explored in high‐quality, multi‐center data sets, with most reports focusing instead on the contribution of isolated high‐risk features to outcomes. 3 , 4 , 6 , 9 , 10 , 11 Other studies have described contributions of multiple risk factors, though with limited outcomes, single center data, or with minimal PAD‐ and procedure‐specific data.…”
mentioning
confidence: 99%
“… 1 Certain characteristics have been demonstrated to confer higher risk of major adverse cardiovascular events (MACE) or major adverse limb events (MALE) following PVI, such as diabetes, 2 , 3 , 4 chronic kidney disease (CKD), 5 , 6 concomitant coronary artery or cerebrovascular disease, 7 , 8 and certain lesion characteristics. 2 , 9 , 10 , 11 However, the relationships between these factors have not been well explored in high‐quality, multi‐center data sets, with most reports focusing instead on the contribution of isolated high‐risk features to outcomes. 3 , 4 , 6 , 9 , 10 , 11 Other studies have described contributions of multiple risk factors, though with limited outcomes, single center data, or with minimal PAD‐ and procedure‐specific data.…”
mentioning
confidence: 99%
“…A study demonstrated that additional angioplasty of poor runoff vessels is beneficial for clinical outcomes of SFA stenting; they defined the runoff according to the number of patent tibial arteries detected on the baseline angiogram. 8 The current study suggests a more precise approach that patients with poor runoff (runoff score >10), may benefit from additional methods to help increase patency such as angioplasty of the runoff tibial vessels, although this clearly requires additional study and validation.…”
Section: Discussionmentioning
confidence: 91%
“…Runoff affects the result of SFA interventions, 8,11,20 but there is little quantitative data describing the impact of runoff on the patency of long-segment SFA stents. We followed up the long-segment stents using ultrasound, determining the quality of the runoff with modified SVS criteria; 13 binary ISR was significantly higher in patients with poor quality outflow vessels (runoff score > 10) (Figure 3(b)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This principle is well known by plumbers and stated in the plumbing principle of the World Health Organisation 1 : "drains should be of adequate capacity and should be designed, constructed and maintained to convey wastewater rapidly from the building without fouling, depositing solids or clogging." Watanabe et al 2 have highlight the validity of this plumbing principle in vascular surgery. The authors compared the outcomes of stenting for femoropopliteal recanalisation according to the runoff status ( 2 patent tibial vessels versus 1 patent tibial vessel).…”
mentioning
confidence: 99%